2022
DOI: 10.1111/jgh.15761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remimazolam tosilate on early cognitive function in elderly patients undergoing upper gastrointestinal endoscopy

Abstract: Background and Aim Remimazolam tosilate (RT) is under evaluation as a sedative for endoscopic procedures. Herein, we aimed to evaluate safety including cognition recovery of RT administered in elderly patients undergoing upper gastrointestinal endoscopy and assess its safety dosage. Methods Ninety‐nine patients presenting for upper gastrointestinal endoscopy were randomized to receive 0.1 mg/kg RT (R1) or 0.2 mg/kg RT (R2), or propofol (P). Cognitive functions (memory, attention, and executive function) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 26 publications
3
46
1
Order By: Relevance
“… 9 Liu also found remimazolam may worsen elderly patients’ postoperative cognitive functions in upper gastrointestinal endoscopy. 32 Like remifentanil, remimazolam, when doses at the top end of the response curve, might appear undesirable desensitization effects and rebound phenomenon once stopped, such as anxiety. 5 Cases about remimazolam tolerance have been reported in benzodiazepine long-term users.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Liu also found remimazolam may worsen elderly patients’ postoperative cognitive functions in upper gastrointestinal endoscopy. 32 Like remifentanil, remimazolam, when doses at the top end of the response curve, might appear undesirable desensitization effects and rebound phenomenon once stopped, such as anxiety. 5 Cases about remimazolam tolerance have been reported in benzodiazepine long-term users.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects all had impacts on the time to full alert. Also, Tian et al indicated that elderly patients who received 0.2 mg/kg remimazolam took significantly longer to recover than propofol in upper gastrointestinal endoscopy [ 34 ]. Besides the age of patients, differences in the administration of remimazolam and the dosage of propofol may lead to the opposite result.…”
Section: Discussionmentioning
confidence: 99%
“…An exploratory analysis suggested more episodes of hypotension when propofol was used for sedation than remimazolam [ 36 ]. Furthermore, a series of studies have shown that remimazolam had more stable hemodynamics and a lower incidence of hypotension in multiple surgical types [ 34 , 37 41 ]. In our study, the incidence of hypotension was lower and a higher average MAP existed in AR groups than AP group.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers administered the sedative drugs intravenously according to the group allocations [a dose of 0.10 mg/kg (R1) or 0.20 mg/kg (R2) RT; or 1.0–1.5 mg/kg propofol]. 39 Differences in the postoperative cognitive functions, sedation times, and recovery times between the patients in the R1 and propofol groups were not statistically significant. The R2 group demonstrated worsened postoperative results than baseline upon immediate recall (−2.79±4.04 vs 1.64±3.97, P<0.001) and short-delayed recall (−0.97±1.83 vs 0.61±1.47, P=0.003).…”
Section: Clinical Usesmentioning
confidence: 99%